2019
DOI: 10.1039/c8sm02634c
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial properties of lipid sponge-like nanoparticles and the role of stabilizer on particle structure and surface interactions

Abstract: Stabilizer P80 concentrated to lipid liquid crystalline particle surface, but contributes also to the inner sponge phase structure. Particles spread on surfaces to form bilayers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 38 publications
3
23
0
Order By: Relevance
“…Finally, from the broad peak position in samples MCH and MCHPC, an internal d -spacing of 6.35 ± 0.02 nm is found. This distance probably represents the characteristic d -spacing of the inverse worm-like micellar structure of the core. , This is consistent with previous results obtained on bulk phase samples …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Finally, from the broad peak position in samples MCH and MCHPC, an internal d -spacing of 6.35 ± 0.02 nm is found. This distance probably represents the characteristic d -spacing of the inverse worm-like micellar structure of the core. , This is consistent with previous results obtained on bulk phase samples …”
Section: Resultssupporting
confidence: 92%
“…The SANS data in Figure A–C were analyzed using either a simultaneous fit for the core–shell sphere model only (sample MMC) or adding a broad peak model to better describe the data in the q range above 0.05 Å –1 (samples MCH and MCHPC). A detailed description of the data analysis can be found in the Supporting Information (SI).…”
Section: Resultsmentioning
confidence: 99%
“…We further characterized the droplets by cryogenic transmission electron microscopy (cryo-TEM) and found that they lack any well-ordered internal structure, consistent with the characteristics of a sponge phase (SI Appendix, Fig. S6A) (30). Deviation from spherical shape is observed likely because of the mechanical stress inherent in the cryo-TEM sample preparation method.…”
Section: Resultsmentioning
confidence: 56%
“…6c, the plot of dissipation versus frequency revealed a kink for 1% DOTAP cubosomes, which may suggest the rearrangement of lipid material. 51
Fig. 6Surface measurements during cubosome uptake measured by QCM-D. a Shift in frequency normalised by overtone (ΔF/ n ) with time.
…”
Section: Resultsmentioning
confidence: 99%